IMPROVED PETROLOGICAL MODAL ANALYSES FROM X-RAY POWDER DIFFRACTION DATA BY USE OF THE RIETVELD METHOD I. SELECTED IGNEOUS, VOLCANIC, AND METAMORPHIC ROCKS - Hill R.J.; Tsambourakis G.; Madsen I.C. (My University, 1993)
Mineral modes have been determined for specimens of eight rock types from CuK? X-ray powder diffraction data using the Rietveld method. The samples include two granites, a granodiorite, adamellite, gabbro, basalt, trachyte, and two granulite-facies metamorphic rocks. Up to eight individual mineral components have been measured in each sample (no glassy phases were observed), with a detection limit of {small tilde}1 wt.%, depending on the mineral assemblage. Marked variations in grain size (i.e., granite vs. trachyte) provide no difficulties for the X-ray method. The X-ray results compare very favourably with (1) optical modes determined for the medium–coarse-grained samples by point counting, (2) normative calculations obtained using locally enhanced catanorm and mesonorm software, and (3) corresponding Rietveld modes determined, for two samples, from neutron powder data. Where differences occur, these are discussed in relation to the limitations of each of the methods. The improved accuracy of the X-ray method is due primarily to the incorporation of the full diffraction profile in the Rietveld analysis calculations, and the elimination of preferred orientation by collecting the data from samples packed in glass capillaries (i.e., Debye–Scherrer mode). The good agreement of the X-ray and neutron modes shows that the usual problems encountered with microabsorption, extinction, and sampling are of little concern in these rocks. The results highlight one of the major advantages provided by Rietveld modal analysis over the more traditional ‘reference intensity’ X-ray methods, namely, that the crystal chemistry (and thus the calibration constants) of the individual phases can be adjusted dynamically during each individual analysis. This not only provides more accurate phase abundances, but also gives important supplementary information about the mineralogy of the major components.